TRAINING ACCOUNTANTS IN HOLLAND AND WEST GERMANY. - Lorig, Arthur N. (The Accounting Review, 1961)
Abstract In Holland and West Germany, accounting as practiced is of good quality as confirmed by American and British Accountants. On the other hand in various countries of western continental Europe accounting has developed rather erratically. This article focuses on the accounting training procedures, which enabled Holland and West Germany to forge well ahead of their neighbors in quality of accounting practice? In comparing the training of accountants in Holland and West Germany with American and British systems, several important differences appeared. The considerable emphasis on Economics, Law and Statistics in the course work of those two countries was obvious. Another difference is supplementing the written examinations with oral examinations. A final major difference is that the training period in the two European countries is longer than the U.S. and England. By studying the accounting systems of these two countries the author questions the validity of hurrying the American trainees into certification.